A study on public perception towards distance learning programs in the institutions of higher learning / James Fidelis Donsia - Donsia, James Fidelis (2007)
The study of public perceptions towards distance learning programs in the institutions of higher learning is an essential to all institution of higher learning. This study is to understand the reasons why public especially working people's perception influenced them to attend distance learning studies, their perceptions towards distance learning and towards the distance learning provider. At the same time, it also evaluated the factors that might influence public decision in the selection of institution of higher learning to attend their distance learning by applying the 7 marketing mix of service. By understanding this will help the higher institution of higher learning to designed their strategy in their distance learning programs that would satisfied the needs and the quality of the distance learning program are according to their future students expectation. Sample of 121 respondents were selected using sample frame. The target populations in this study are the public which consist of working people who are currently doing or have completed their distance learning courses. The selection of the respondent is based on convenience sampling technique, which is the simple random sampling. Towards the end of this study, gather suggestions from the respondents that can be used by the institution of higher learning can be consider in improving their distance learning programs in the future to make students feels enrolling in distance learning is value for their money invested besides fulfilling their needs to obtain a higher education qualification.